POLITIK IDENTITAS TIONGHOA DAN MULTIKULTURALISME PADA FILM NGENEST “KADANG HIDUP PERLU DITERTAWAKAN”: CHINESE IDENTITY POLITICS AND MULTICULTURALISM IN NGENEST FILM "SOMETIMES LIFE NEEDS TO BE LAUGHED AT" - Azzahra, Maharani; Fahrozi; Kustiawan; Sabrina, Rayhan; Sabrina, Rapika (Jurnalika : Jurnal Ilmu Komunikasi, 2024)
This scientific aim is to analyze the occurrence of identity politics and multiculturalism in Indonesia (study of the NGENEST film "Sometimes Life Needs to be Laughed at"). The problem in this research is "How Identity Politics and Multiculturalism in Indonesia are seen from the NGENEST Film "Sometimes Life Needs to be Laughed at". The results of this research emphasize that identity politics can influence social interactions and often lead to conflict. The change in Meira's papa's attitude towards Ernest reflects how prejudice and stereotypes can be overcome. This research is included in qualitative research by connecting objects or symptoms of conditions with the culture in question. The approach used is literature study.